Antibiose relacionada a cultivo de Lactobacillus acidophilus. 2. Otimização de alguns parâmetros de cultivo em meio à base de soro de queijo e extrato aquoso de soja - Pinto, Marcos Franke [UNESP]; Giglio Ponsano, Elisa Helena; Castro-Gómez, Raul Jórge Hernán (My University, 1996)
Whey supplemented with soy milk has been used as a low-cost alternative in the growth of Lactobacillus acidophilus for the production of antimicrobial compounds. Response Surface Metodology has been employed in order to study the effects of initial pH, incubation temperature and soy milk rate for supplementation in the production of antimicrobial substance. It has been observed that both tested microrganisms used (S. aureus and E. coli) were inhibited by antimicrobial substance produced by L. acidophilus. The results obtained with E. coli inhibition did not follow the employed statistical model. On the other hand, when the tested microorganism S. aureus was used, the best inhibition results have been obtained when L. acidophilus was incubated at 36.80°C in whey with 5.6 initial pH and 31,90% (v/v) rate supplemented with soy milk. The analysed antimicrobial substances were nor acids neither hidrogen peroxid.
Antibiosis associated to Lactobacillus acidophilus growth. 2. Optimization of some culture parameters in whey and soy milk medium
Keywords: Antibiosis; Lactobacillus acidophilus; Response surface metodology; Soy milk; Whey